Age-related differences in cognitive function for interlimb coordination during split-belt walking: A pilot study. (March 2013) - Saito, Mayumi; Hyodo, Masaki; Masakado, Yoshihisa; Tomita, Yutaka; Ushiba, Junichi
<x xml:space="preserve">Abstract</x> While walking is considered a task demanding cognitive functions rather than an automatic motor task, it is still unclear whether cognitive tasks influence interlimb coordination during walking. The present study revealed that the elderly require cognitive function to control temporal interlimb coordination under difficult walking conditions. Risk of falls is thus likely to be increased in the elderly when performing attention-demanding tasks while walking.